Land Assets PT. Panca Wira Usaha is owned by a Local Company in East Java Province, Occupied by the Community - Karyoto, Karyoto; Sisbiantoro, Dwi; Talkah, Abu (Prosiding Seminar, 2023)
When the VOC came to Indonesia around 1577 with the intention to trade and made the kingdom of Mataram a protectorate and since then the role of local officials gradually began to change. The arrival of VOC in Indonesia aims for the following matters: Prevent competition among Dutch traders Obtain a trade monopoly in south Asia or exclusively master the spices both in producing and trading so how the status of people was in that land at PT. Panca Wira Usaha. The study was qualitative with case study of PT. Paca Wira Usaha. VOC as a Dutch-owned legal entity engaged in trade, it is a little more know the public legal aspects as the influence of Roman law, although no relation belongs to the land, but VOC make agreements with the landowners as if to voc charge as an obligation to rent land through an agreement that is essentially so that the visible aspect of democracy appears. The Dutch Government established factories in big cities after the VOC successfully mastered inland village for agriculture, plantation and others. One of the factory is Oil Factory "N. V OLIEFABRIEKEN INLINDIE" or known as "Pabrik Minyak Nabati-Yasa PT Panca Wira Usaha", located in Kediri City Government of East Java Province, which is currently a problem between PT. Panca Wira Usaha, East Java Provincial Government Owned Enterprises with the Community of the landowners. The main issue is the provisions of the Law regulating the Dutch Heritage Company, such as Law No. 86 Of 1958 about the nationalization of Dutch-owned enterprises in Indonesia, not supported by UUPA No. 5 Of 1960 on the basic rules of agrarian basic . While UUPA No. 5 Of 1960 has not been clear in explaining and describing the meaning and substance of the land of the former western rights of the Dutch company, resulting in land tenure by the community. The community can continue to occupy land and houses, as long as they pay rent, through a bank account in the name of PT. Panca Wira Usaha.